Normal girl a novel - Jong-Fast, Molly 1978- (A Sceptre Book, 2000)
Miranda is young, rich and famous, frantically filling the void at the centre of her life with a high-voltage cocktail of designer people, designer labels and designer drugs. But Jeff's death makes Miranda think again. After all, this girl doesn't want to be an afterthought before she's 20